ENGLISH AS FOREIGN LANGUAGE (EFL) STUDENTS’ PERCEPTION OF AI WRITING TOOLS BASED ON THEIR EDUCATION LEVEL - Annishah Annishah; Utami Widiati; Anik Nunuk Wulyani (Premise: Journal of English Education and Applied Linguistics, 2025)
EFL students at any level of education are nowadays accustomed to using AI tools to support their English learning. They also use it during academic writing. Understanding the perception is therefore important to optimize the use of AI writing tools. Â The existing literature suggests that there are contrasting perceptions among students. Hence, this study aims to uncover the perceptions and uses of AI writing tools used by EFL students from different levels of education, which are undergraduate and master’s degree. This study utilized a mixed method combining surveys and interviews to answer research questions. The result suggests that the difference lies in the varieties of tools used by each level of education. Master’s degree tends to use more diverse AI writing tools compared to an undergraduate. As for the perception, both levels perceived AI writing tools positively. Suggestions for further studies are also presented in the last section. This study contributes to the developing area of AI in education and provides insight on how different levels of education utilize AI writing tools. Â Â